Early Clinical Mapping of Submandibular Gland Fistula: A Case Report and Systematic Review - Vivek Dokania; Md Ibrar; Mayashankar Vishwakarma (International Archives of Otorhinolaryngology, 2024)
Introduction Submandibular gland fistula (SGF) is a rare subset of salivary gland fistulas. It is seldom tough to diagnose them prior to surgical exploration, and it is often clinically confused with close differentials. An early diagnosis based on pertinent clinical features and focused radiological findings can be pivotal in optimal management and help prevent recurrence and avoid unnecessary investigations/interventions.